Efficacy and safety of traditional Chinese classic prescriptions combined with metformin in the treatment of type 2 diabetes mellitus: a Bayesian network meta-analysis - Che, Linlin; Dong, Wei; Liu, Ya; Guo, Hongwei (Frontiers in Pharmacology, 2026)
BackgroundType 2 diabetes mellitus (T2DM) is a metabolic disorder characterized by chronic hyperglycemia. While biomedicine (e.g., metformin) serves as the first-line treatment, combination therapies involving botanical drugs are increasingly utilized. However, the comparative efficacy of different botanical formulations remains to be systematically evaluated.AimThis study aims to analyze randomized controlled trials (RCTs) to evaluate the clinical efficacy and safety of eight specific classical botanical drug formulas combined with metformin (Met) for T2DM, providing evidence to support integrated clinical management.MethodsA Bayesian network meta-analysis (NMA) was performed on RCTs sourced from PubMed, Cochrane Library, Embase, Web of Science, and Chinese databases. The taxonomic validation of all botanical drugs was conducted using MPNS. Outcomes including HbA1c, FPG, and lipid profiles were assessed using the SUCRA and GRADE methodology.ResultsForty RCTs involving 3,088 patients were included. In terms of glycemic control, the combination of Huanglian Jiedu Decoction (HLJDD) and Met ranked highest for reducing FPG [MD = −1.46, 95% CrIs=(−2.24, −0.68)], while HLJDD, Zhibai Dihuang Decoction (ZBDHD), and Dachaihu Decoction (DCHD) combined with Met emerged as the most effective for reducing HbA1c. Notably, sensitivity analysis restricted to trials ≥8 weeks identified HLJDD [MD = −1.02, 95% CrIs=(−1.39, −0.66)] and ZBDHD [MD = −1.02, 95% CrIs=(−1.28, −0.76)] as the most robust interventions for long-term glycemic control. Safety reporting was limited, with only 8 out of 40 trials (20.0%) providing data on adverse events. While no severe adverse events were reported in these specific trials, the overall safety evidence remains uncertain due to substantial missingness and potential under-reporting.ConclusionThe current NMA results suggest that HLJDD combined with Met is a consistently effective option for reducing both FPG and HbA1c. For HbA1c improvement, while DCHD combined with Met showed initial potential, sensitivity analysis restricted to trials ≥8 weeks identified HLJDD and ZBDHD as the most physiologically robust interventions. However, given the “Very Low” certainty of evidence for many comparisons, these rankings remain exploratory.